(untitled) (CIPEEX, 2023)
The objective of the study was to evaluate the influence of biomimetic conditioning (BC) (prior endodontic sealing associated with deep margin elevation and restoration of cavities) of the tooth prior to root canal treatment on the fracture resistance, mode of failure, and stresses and deformations of molars with extensive MOD cavities restored with provisional restorative material. Four groups were obtained and analyzed using the three-dimensional finite element method (in silico) and also in vitro: G1- Inlay; G2– Onlay; G3– CB inlay; and G4- CB onlay. A load of 100N was applied to the occlusal surface of the crown and the maximum principal stress (σmax), shear stress (tmax), and maximum principal displacement (umax) were checked for all the involved structures. For the in vitro study, a spherical tip with a diameter of 6 mm was centrally positioned on the occlusal surface of the tooth, and a compressive load was applied (1 mm/min) until fracture. The models with CB showed a reduction in stress and strain values compared to the models without CB, which had the stresses concentrated at the bases of the cusps. The inlay group showed the lowest fracture load values (879.9 N ±192.92), followed by the onlay group (1201.2 ±136.83), inlay+CB (1390.8 ±195.18), and the highest value was found in the onlay+CB group (1631.3 ±211.54). There was no statistical difference (p=0.123) between the onlay group and the inlay+CB group. The Biomimetic Conditioning pre-endodontic treatment increased the fracture resistance of endodontically treated molars.